What do children write?, a glance at the new school model - Bernal-Pinzón, Mary Luz (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article presents the results of a research that aimed to know what girls and boys from primary school write. It implied a glance at their experiences in a rural context, considering the guidance of “New School”, a method of work that the teacher manages using guides. The process was carried out keeping in mind an action research methodology, allowing not only to investigate how girls and boys understand and construct written language, but to reflect on how the teacher focuses her methodology. The theoretical perspective of the natural method of Freinet served as a framework to recognize in the children’ texts a material that could be considered as valid, redirected in order to understand the children’ writing, with the possibility of taking into account the world around them. It was also achieved a new meaning to the guides as a way to facilitate children’ learning from a “free text” approach.